PENGETAHUAN TENAGA KEPENDIDIKAN TERHADAP PENGGUNAAN MOUSE DAN KEYBOARD SECARA ERGONOMI DI UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA - Sunyanti Sunyanti (Program Studi D-IV K3, 2019)
University of Sembilanbelas November Kolaka is a new state college. The new public universities absorb a lot of educational power and have a large scope of work. University of Sembilanbelas November Kolaka it is young to be aware of the work facilities and the setting of a good and healthy working environment. The University of Sembilanbelas November Kolaka is also very concerned also in intensive good working standards, but the University of Sembilanbelas November Kolaka has not noticed whether education personnel use keyboards and mice ergonomic or not ergonomic. There is a relationship between educational knowledge level to the use of mouse and keyboard ergonomics at the University of Sembilanbelas November Kolaka. The analysis Model used is a simple linear analysis. There is a relationship between the educational knowledge level to the use of mouse and keyboard ergonomics in the scope of the University of Sembilanbelas November Kolaka. From the value of coefficient the relationship in the gain R count (0.850) > R table (0.340) with a significance level of 5% (N = 30), then in this cased has a very strong value. There is a specific approach that exists in the discipline of ergonomics is the systematic application of all relevant information relating to the characteristics and behaviours in the design of equipment, facilities and work environment that used. We recommend training about the ergonomics of office information Systems, which is done at least 1 year 2 times and Applied safety campaign about ergonomics in the computer office information System, the existence of safety sign or delivery at the time or joint meeting of the principal.